Poradnie małżeńsko-rodzinne w diecezji w aspekcie kanoniczno-duszpasterskim - Adamczyk, Jerzy (Ius Matrimoniale, 2016)
The author of the following article focused on the issue of marriage-family counseling centers in the diocese from the canonic-pastoral point of view. The aim of this article was to present the necessity of the existence of various kinds of marriage-family counseling centers in the diocese. Firstly, the marriage-family counseling center has been presented, then the issue of deanery and regional counseling center has been discussed, and finally, the parish counseling center has been depicted.